Fiber raw material pretreatment method for improving bulk while ensuring tensile strength of paper

By microwave pretreating the wood fiber raw material, a stable carbon-carbon bond structure is formed, which solves the problem of sacrificing tensile strength when increasing the loose thickness of the pulp in the prior art, and achieves the effect of improving the loose thickness of the pulp without affecting the strength.

CN119610316APending Publication Date: 2025-03-14INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510003953.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Prior art usually requires sacrificing the tensile strength of the paper while increasing the loose thickness of the pulp.

Method used

By processing the ligno fiber raw materials into filamentous materials and microwave pretreatment under a protective atmosphere, the active points in the lignin are stimulated to form free radicals, and condensation forms a structurally stable carbon-carbon bond structure, thereby improving the structural strength of the lignin in the fiber raw materials.

Benefits of technology

While ensuring the tensile strength of the paper, the looseness of the pulp is increased, which is specifically manifested as the increase in the thickness is between 5.67% and 10.57% when the strength is basically unchanged.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a fiber raw material pretreatment method capable of improving the bulk while ensuring the tensile strength of paper. The method comprises the following steps: processing a wood fiber raw material into a filamentous material; the filamentous materials are subjected to microwave pretreatment under the condition of a protective atmosphere, the materials subjected to microwave pretreatment are prepared into chemimechanical pulp, then the chemimechanical pulp is prepared into paper, and the bulk of the obtained paper can be improved while the tensile strength is guaranteed. According to the method, chemimechanical pulp is pretreated through microwaves, active sites such as the site 2 and the site 5 of a G unit in an internal structure of lignin and the site beta of a lignin side chain structure are excited to form free radicals through the heat effect of the microwaves, and then a carbon-carbon bond structure with a stable structure is formed through condensation of the free radicals; the purpose of reinforcing the lignin structure in the fiber raw material is achieved, the removal rate of the lignin in the follow-up pulping process is reduced, the lignin content of paper pulp is increased on the premise that exposure of microfilaments is not affected and the paper strength is guaranteed, and then the bulk of paper is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of pulping technology, and in particular to a fiber raw material pretreatment method for improving the bulk while ensuring the tensile strength of paper. Background Art

[0002] In recent years, the production and consumption of packaging paper, boxboard and corrugated paper have been increasing year by year. Bulk thickness, as the most important performance index of packaging paper and paperboard, is currently mainly provided by chemical mechanical pulp (hereinafter referred to as chemical mechanical pulp). Bulk thickness is the volume of paper or paperboard per unit mass. Generally speaking, the higher the lignin content in the pulp, the higher the bulk thickness. The strength index is the first attribute of pulp performance, and all paper products have certain requirements for pulp strength. Generally speaking, for chemical mechanical pulp, the lower the lignin content in the pulp, the more fully the microfibrils in the raw material are exposed, and the more alcohol hydroxyl groups that can form hydrogen bonds, the better the strength. Therefore, the lignin content in the pulp determines the balance between the bulk thickness and strength of chemical mechanical pulp. The higher the lignin content, the higher the bulk thickness and the lower the strength; the lower the lignin content, the lower the bulk thickness and the higher the strength.

[0003] At present, the main methods to increase the bulk of pulp are: 1. Reduce the amount of sodium hydroxide used in the pulping process and increase the lignin content in the pulp. This will inevitably reduce the exposure of microfibrils and affect the strength of the paper. 2. Add bulk enhancers, also known as debonding agents, during the papermaking process. They are generally tertiary amines or quaternary ammonium salt surfactants. The principle is to cover the alcohol hydroxyl groups of pulp fibers with hydrophobic molecules to reduce hydrogen bonding. 3. Graft copolymerization of hydrophobic groups on the pulp to reduce hydrogen bonding. In summary, the existing technical solutions all use the means of reducing the exposure of microfibrils or covering the exposed microfibrils as a means to increase bulk at the expense of pulp strength. Summary of the invention

[0004] The object of the present invention is to provide a fiber raw material pretreatment method for improving the bulk while ensuring the tensile strength of paper, so as to solve the problems in the prior art.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A fiber raw material pretreatment method for improving the bulk while ensuring the tensile strength of paper comprises the following steps:

[0007] Processing wood fiber raw materials into filamentous materials; the wood fiber raw materials include but are not limited to chemical mechanical pulp fiber raw materials such as eucalyptus, poplar, acacia, pine, bamboo, etc.; the dryness of the filamentous materials needs to be controlled at more than 50%, and the best effect is more than 85%.

[0008] The filamentous material is subjected to microwave pretreatment under a protective atmosphere to obtain a pretreated material; the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere such as helium or argon; the yield of the material after microwave pretreatment is controlled to be no less than 98.5%;

[0009] The pretreated material is prepared into chemical mechanical pulp and then made into paper, and the obtained paper can improve the bulk while ensuring the tensile strength; the method for preparing the pretreated material into chemical mechanical pulp is: firstly subjecting the pretreated material to alkali treatment, and then refining the pretreated material with a disc refiner to a Canadian freeness of 300±25mL CSF to obtain chemical mechanical pulp.

[0010] A further solution is to process the wood fiber raw material into a filamentous material by first making the wood fiber raw material into wood chips, the length of the wood chips being 20mm-50mm, the width being 5mm-20mm, and the thickness being 3mm-8mm; then the wood chips are made into a filamentous material by mechanical extrusion, and then dried at a temperature of 105°C to a dryness greater than 50%.

[0011] In a further embodiment, the power of the microwave pretreatment is 10-50 kilowatts / kg, the time of the microwave pretreatment is 1-5 minutes, the number of microwave pretreatments is 4-15 times, and after each microwave pretreatment is completed, the obtained material is fully mixed before the next treatment.

[0012] In a further embodiment, the alkali treatment process is as follows: adding the pretreated material to a sodium hydroxide solution to obtain a mixed slurry, and then heat-treating the mixed slurry at a temperature of 80°C-95°C for 1 hour, wherein the mass fraction of the pretreated material in the mixed slurry is 20-30%;

[0013] The present invention has the following beneficial effects:

[0014] The present invention utilizes microwaves to pretreat chemical mechanical pulp. Through the thermal effect of microwaves, the heat energy generated by the frequent friction between a small amount of water molecules and polar groups such as carboxyl and hydroxyl groups in the raw materials under the microwave electromagnetic field is utilized to excite active sites such as the 2nd and 5th positions of the G unit in the internal structure of lignin and the β position of the lignin side chain structure to form free radicals. The condensation of the free radicals is then utilized to form a structurally stable carbon-carbon bond structure. The purpose of strengthening the lignin structure in the fiber raw material is achieved without changing the microfibril structure and the exposure degree, so as to reduce the removal rate in the subsequent pulping process, and to increase the bulk of the pulp without affecting the exposure of the microfibrils and ensuring the strength of the paper.

[0015] It should be noted that microwave treatment should be carried out in a short time and multiple times, otherwise local overheating of the pulp will lead to carbonization or even combustion. The appropriate degree of microwave treatment can be controlled by controlling the yield of the material after microwave treatment. At the same time, after the material is heated to generate free radicals, the condensation reaction between the free radicals mainly occurs in the cooling stage. Therefore, multiple excitation-cooling-mixing treatments are conducive to a more uniform distribution of new carbon-carbon bonds in the material. Microwave treatment must be carried out in an anaerobic state, otherwise relatively unstable carbon-oxygen ether bonds will be formed during the condensation of free radicals, and the effect of reducing the lignin removal rate in the subsequent pulping process cannot be achieved. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with the embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0017] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional means in the prior art in the art, and therefore, they are not described in detail; the raw materials used are all commercially available products.

[0018] Example 1

[0019] Using Eucalyptus grandis as raw material, after being processed by a chipper and passed through a wood chip screen, qualified wood chips with a length of 20mm-50mm, a width of 5mm-20mm, and a thickness of 3mm-8mm are obtained, and then processed into filaments (material A) by a twin-screw pulper. Bake at 105°C until the moisture content is 90%. Under nitrogen protection, use a power of 30 kW / kg, each treatment for 3 minutes, and a total of 4 treatments. After each treatment, mix the material thoroughly. The yield of the material (material B) after microwave treatment is 99%. Take material A and material B at a concentration of 20%, the amount of sodium hydroxide is 20kg / t of absolute dry pulp, and treat at 95°C for 1h. After the reaction is completed, wash the material and grind it to a Canadian freeness of 300mL CSF by a disc mill. According to the relevant national standards, the pulp obtained from material A and material B is made into a quantitative 60g / m 2 The bulk thickness of material A was measured to be 2.55 cm 3 / g, tensile strength is 0.74kN / m; the bulk thickness of material B is 2.72cm 3 / g, tensile strength is 0.76kN / m. While the strength remains basically unchanged, the bulk thickness increases by 6.67%.

[0020] Example 2

[0021] Using triploid white poplar as raw material, after being processed by chipper and screened, qualified wood chips with length of 20mm-50mm, width of 5mm-20mm and thickness of 3mm-8mm are obtained, and then processed into filamentous balls (material C) by twin-screw extruder. Bake at 105℃ until the moisture content is 90%. Under the protection of helium, use 50 kW / kg power, each treatment for 4 minutes, a total of 8 treatments, and fully mix the materials after each treatment. The yield of the material (material D) after microwave treatment is 98.5%. Take material C and material D at a concentration of 25%, the amount of sodium hydroxide is 30kg / t of absolute dry pulp, and treat for 1h at 95℃. After the reaction is completed, wash the material and grind it to Canadian freeness 320mL CSF by disc mill. According to the relevant national standards, the pulp obtained from material C and material D is made into a quantitative 60g / m 2 The bulk thickness of material A was measured to be 2.82 cm 3 / g, tensile strength is 1.56kN / m; the bulk thickness of material B is 2.98cm 3 / g, tensile strength is 1.55kN / m. While the strength remains basically unchanged, the bulk thickness increases by 5.67%.

[0022] Example 3

[0023] Acacia crassicarpa was used as the raw material. After being processed by a chipper and passed through a wood chip screen, qualified wood chips with a length of 20mm-50mm, a width of 5mm-20mm, and a thickness of 3mm-8mm were obtained, and then processed into filamentous balls (material E) by a twin-screw pulper. Bake at 105°C until the moisture content is 90%. Under argon protection, use a power of 10 kW / kg, treat for 3 minutes each time, and treat 15 times in total. After each treatment, mix the material thoroughly. The yield of the material (material F) after microwave treatment is 98.8%. Take material E and material F at a concentration of 22%, a sodium hydroxide dosage of 10kg / t absolute dry pulp, and treat at 80°C for 1h. After the reaction is completed, wash the material and grind it to a Canadian freeness of 300mL CSF by a disc mill. According to the relevant national standards, the pulp obtained from material E and material F is made into a quantitative 60g / m 2 The bulk thickness of material E was measured to be 3.12 cm 3 / g, tensile strength is 0.66kN / m; the bulk thickness of material F is 3.45cm 3 / g, and the tensile strength is 0.66kN / m. While the strength remains basically unchanged, the bulk thickness increases by 10.57%.

[0024] Example 4

[0025] Use Masson pine as raw material, after being processed by chipper and screened, qualified wood chips with length of 20mm-50mm, width of 5mm-20mm and thickness of 3mm-8mm are obtained, and then processed into filamentous balls (material G) by twin-screw pulping machine. Bake at 105℃ until the moisture content is 90%. Under nitrogen protection, use 50 kW / kg power, each treatment for 5 minutes, a total of 5 times, and the material needs to be fully mixed after each treatment. The yield of the material (material H) after microwave treatment is 99.3%. Take material G and material H at a concentration of 20%, the amount of sodium hydroxide is 50kg / t of absolute dry pulp, and treat for 1h at 95℃. After the reaction is completed, wash the material and grind it to Canadian freeness 280mL CSF by disc mill. According to the relevant national standards, the pulp obtained from material G and material H is made into a quantitative 60g / m 2 The bulk thickness of material G was measured to be 3.41 cm 3 / g, tensile strength is 1.82kN / m; bulk thickness of material H is 3.62cm 3 / g, tensile strength is 1.80kN / m. While the strength remains basically unchanged, the bulk thickness increases by 6.15%.

[0026] Example 5

[0027] Use bamboo as raw material, after being processed by chipper and screened, qualified wood chips with length of 20mm-50mm, width of 5mm-20mm and thickness of 3mm-8mm are obtained, and then processed into filamentous balls (material I) by twin-screw pulping machine. Bake at 105℃ until the moisture content is 90%. Under nitrogen protection, use 30 kW / kg power, each treatment for 2 minutes, a total of 10 times, and mix the materials thoroughly after each treatment. The yield of material (material J) after microwave treatment is 99.2%. Take material I and material J at a concentration of 30%, the amount of sodium hydroxide is 20kg / t of absolute dry pulp, and treat for 1h at 95℃. After the reaction is completed, wash the material and grind it to Canadian freeness 310mL CSF by disc mill. According to relevant national standards, the pulp obtained from material I and material J is made into a quantitative 60g / m 2 The bulk thickness of material I was 2.75 cm 3 / g, tensile strength is 0.48kN / m; the bulk thickness of material J is 2.99cm 3 / g, tensile strength is 0.46kN / m. While the strength remains basically unchanged, the bulk thickness increases by 8.73%.

[0028] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A fiber raw material pretreatment method for increasing the bulk while ensuring the tensile strength of paper, characterized in that: The following steps are involved: Processing wood fiber raw materials into filamentous materials; The filamentous material is subjected to microwave pretreatment under a protective atmosphere to obtain a pretreated material; The pretreated material is prepared into chemical mechanical pulp and then made into paper; the paper can increase the bulk while ensuring the tensile strength.

2. A fiber raw material pretreatment method for improving the bulk while ensuring the tensile strength of paper according to claim 1, characterized in that: The wood fiber raw material includes at least one of eucalyptus, poplar, acacia, pine and bamboo.

3. A fiber raw material pretreatment method for improving the bulk while ensuring the tensile strength of paper according to claim 1, characterized in that: The method for processing wood fiber raw materials into filamentous materials is as follows: firstly, the wood fiber raw materials are made into wood chips, and then the wood chips are made into filamentous materials through mechanical extrusion treatment.

4. A fiber raw material pretreatment method for increasing the bulk while ensuring the tensile strength of paper according to claim 3, characterized in that: The length of the wood chip is 20mm-50mm, the width is 5mm-20mm, and the thickness is 3mm-8mm.

5. A fiber raw material pretreatment method for improving the bulk while ensuring the tensile strength of paper according to any one of claims 1 to 4, characterized in that: The dryness of the filamentous material needs to be controlled above 50%.

6. A fiber raw material pretreatment method for increasing the bulk while ensuring the tensile strength of paper according to claim 1, characterized in that: The protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.

7. A fiber raw material pretreatment method for increasing the bulk while ensuring the tensile strength of paper according to claim 1, characterized in that: The power of the microwave pretreatment is 10-50 kilowatts / kg, and the time of the microwave pretreatment is 1-5 minutes; the number of microwave pretreatments is 4-15 times, and after each microwave pretreatment, the obtained material is fully mixed before the next treatment; The material yield after microwave pretreatment is controlled to be no less than 98.5%.

8. A fiber raw material pretreatment method for increasing the bulk while ensuring the tensile strength of paper according to claim 1, characterized in that: The method for preparing the pretreated material into chemical mechanical pulp is: firstly subjecting the pretreated material to alkali treatment, and then refining the pretreated material through a disc refiner until the Canadian freeness is 300±25 mL CSF, so as to obtain chemical mechanical pulp.

9. A fiber raw material pretreatment method for increasing the bulk while ensuring the tensile strength of paper according to claim 8, characterized in that: The alkali treatment process is as follows: adding the pretreated material to a sodium hydroxide solution to obtain a mixed slurry, and then performing a heat preservation treatment at a temperature of 80° C.-95° C. for 1 hour, wherein the mass fraction of the pretreated material in the mixed slurry is 20-30%.

Citation Information

Patent Citations

  • Procedure for improving properties of mechanical wood pulps

    CA1145106A

  • Methods of processing biomass comprising electron-beam radiation

    CA2823243A1

  • Pulping process and paper pulp manufactured in same

    CN103352384A

  • Method for preparing monophenol compounds through microwave depolymerization of lignin

    CN107337585A

  • Filter paper added with sulfur-loaded coconut-shell activated carbon and used for automobile filter, and preparation method thereof

    CN107338681A